2015
DOI: 10.1002/ps.3958
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution and frequencies of organophosphate‐resistant Ace alleles and morphometric variations in olive fruit fly populations

Abstract: The frequencies and geographic range of resistance alleles indicate that they were selected in the Aegean coast of Turkey and then spread westward towards Europe. One possible explanation for the absence of morphological asymmetry in olive fly samples might be the presence of modifier allele(s) that compensate for the increase in asymmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The differences were attributed to recent introduction of resistant alleles. However, differences in frequencies of resistant associated alleles were found in Turkey as well (Doğaç et al, 2015), possibly due to local specificity of insecticides use. Another interesting finding was observed by the same authors who identified higher frequency of Δ3Q mutation in a region with lower frequencies of the other two mutations.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The differences were attributed to recent introduction of resistant alleles. However, differences in frequencies of resistant associated alleles were found in Turkey as well (Doğaç et al, 2015), possibly due to local specificity of insecticides use. Another interesting finding was observed by the same authors who identified higher frequency of Δ3Q mutation in a region with lower frequencies of the other two mutations.…”
Section: Discussionmentioning
confidence: 97%
“…All previous observations of several authors identified Δ3Q to be always in a heterozygous state. However, Doğaç et al (2015) identified one homozygous sample in the Hatay and one in the Aydin populations.…”
Section: Frequency Of δ3q Mutationmentioning
confidence: 94%
See 2 more Smart Citations
“…The current knowledge on genetic resistance status for olive fruit flies field populations is only available for a few specific regions. Olf carrying resistant alleles to OPs has been observed in field populations from Greece, Italy, Cyprus and Turkey [16][17][18][19][20]. Indeed, the frequencies reported for IV-VII exons resistant alleles encompassed values between 69%-90% for Greek populations, between 75%-83% for Italian and about 68% for Turkish populations [16,18,20].…”
Section: Introductionmentioning
confidence: 99%